Reimagining Leadership in the Era of Power Balance: How an Empowered Workforce Is Shifting Traditional Dynamics - Aoun, Cathy-John (Digital Repository of Theses - SSBM Geneva, 2025)
This research originates from a critical reflection on the evolving power dynamics between leaders and employees in the digital era. Employees today are increasingly equipped with advanced knowledge, direct access to information, and digital tools. They also have an amplified online visibility, which turns their voice into impact. These capabilities challenge traditional pyramidal organizations that consider employees as followers of decisions. Moreover, statistics and global trends indicate that employees are displaying a global low engagement in their jobs. Macro phenomena such as the rise in freelancing and entrepreneurial aspirations, and post-pandemic trends like the “Great Resignation,” push to reconsider the value proposition of traditional employment. These trends indicate a shift in employees’ values towards autonomy, flexibility, and purpose. The extensive existing literature on leadership considers employee empowerment as an outcome of effective leadership and organizational culture. It rarely treats it as an observable fact. As business landscape is transforming, companies should adapt to avoid stagnation, reduced innovation, loss of young talent, and employee disengagement. To address this gap, this research adopts a mixed-methods approach to explore Power Balance. This perspective does not present shared leadership as an HR strategy; rather, it recognizes it as an observable element of modern landscape. It reflects a reality in which autonomous, informed, visible and capable employees can influence organizational outcomes regardless of formal rank. This thesis proposes a more comprehensive and even understanding of influence in the digital age. To deepen the exploration of this concept, insights from secondary data were collected, complemented by a survey composed of 14 Likert-scale statements and one qualitative question, sent to 205 voluntary participants working for the UK private sector. The results ultimately indicated ambiguous feelings towards power balance. Although the gap between leadership and employees is narrower, balance is not reached yet, but technological advancements suggest progress. Employees recognize their newly earned powers but still have difficulties in considering their influence on par with leadership’s. This indicates that technology alone is not sufficient; there is a deep cultural change that ought to be made, and effective leadership strategies must be implemented to foster mutual recognition of power.